Strategi Pengembangan Pembiayaan Mikro PT Bank Negara Indonesia Syariah Kantor Cabang Bekasi Menggunakan Metode SWOT Dan ANP - Putra Aditya Masrur; Fajri Ryan Isndandar (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
This study aims to provide recommendations for alternative strategic priorities in the context of developing microfinance for PT BNI Syariah Kantor Cabang Bekasi. This research method uses the SWOT matrix analysis method and the ANP (Analytic Network Process) method which is processed with super decision software and Microsoft Excel. Respondents in this study amounted to three internal practitioners from PT BNI Syariah Kantor Cabang Bekasi, namely business manager, micro account officer head and junior micro financing risk. The results showed that the human resource aspect of (0.421) was the influential aspect. That human resources are valuable assets in holding the success of a company or business. The problem shows that the lack of human resources who serve as micro AOs (Account Officers) is the main problem that has an important impact of (0.209) this can be seen from the number of only 2 people consisting of micro account officers and junior micro financing risk. While the priority alternative strategy with a value of (0.196) is to expand market share by conducting activities or opening outlets in trade centers, because if the market share of PT BNI Syariah Kantor Cabang Bekasi micro-financing products increases then of course demand will also increase.